Desempenho térmico de cobertura vegetada sobre guarita de fibra de vidro exposta a diferentes condições climáticas em Curitiba - Kaviski, Francine (2018)
This study aims to evaluate the thermal performance of a vegetated roof in a fiberglass security booth for the spring-summer climatic conditions of Curitiba / PR. The methodology was based on the comparison of an experimental module (EM) against a control module (CM) for five different configurations of the green-roof system (substrate, substrate and vegetation, substrate, vegetation and shading screen) and window conditions (open and closed). The monitoring of air temperature, surface and air humidity variables was performed between spring 2017 and summer 2018. The thermal comfort / thermal stress analysis followed normative parameters of the wetbulb globe temperature index (WBGT) and the effective-temperature index (ET). It was found that the fiberglass booth, due to its low thermal mass, interferes directly with the air temperature in both modules. The green roof in EM reduced thermal fluctuation with time-lag effect in terms of surface temperatures. Internal surface temperature reduced by up to 12.1°C when compared to CM. The hours equal to or greater than 30°C WBGT were null, ensuring comfort conditions indoors, the same occurring with the values obtained for the ET coefficient, which remained within the comfort range at 21 % of the total monitored hours. Finally, thermal stratification in ME could be attributed to the substrate’s thermal capacity and vegetation cover and to the shading mesh.